2015
DOI: 10.1021/jf506307x
|View full text |Cite
|
Sign up to set email alerts
|

Decoding the Combinatorial Aroma Code of a Commercial Cognac by Application of the Sensomics Concept and First Insights into Differences from a German Brandy

Abstract: In the volatile fraction isolated from a commercial Cognac by means of extraction/SAFE distillation, 39 odor-active areas were detected, among which (E)-β-damascenone showed the highest flavor dilution (FD) factor of 2048 followed by 2- and 3-methylbutanol, (S)-2-methylbutanol, 1,1-diethoxyethane, ethyl methylpropanoate, and ethyl (S)-2-methylbutanoate, as well as 4-hydroxy-3-methoxybenzaldehyde (vanilla-like) and 2-phenylethanol. The quantitation of 37 odorants by stable isotope dilution assays and a calculat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 27 publications
1
48
0
1
Order By: Relevance
“…Supplementary Materials: The following are available online at https://www.mdpi.com/2311-5 637/7/1/21/s1, Table S1: Typical concentrations of the major volatile compounds found in rum produced from sugar cane molasses, alongside their odour threshold and odour activity value (OAV). Structures are from ChemSpider (http://www.chemspider.com/), ref [97][98][99][100][101][102][103] are cited in the supplementary materials file.…”
Section: Future Directions and Conclusionmentioning
confidence: 99%
“…Supplementary Materials: The following are available online at https://www.mdpi.com/2311-5 637/7/1/21/s1, Table S1: Typical concentrations of the major volatile compounds found in rum produced from sugar cane molasses, alongside their odour threshold and odour activity value (OAV). Structures are from ChemSpider (http://www.chemspider.com/), ref [97][98][99][100][101][102][103] are cited in the supplementary materials file.…”
Section: Future Directions and Conclusionmentioning
confidence: 99%
“…Known ligands of chemosensory receptors mainly come from the flavour chemistry, synthetic or natural compounds with well-defined sensory properties. The recently developed “sensomics” approach has led to the identification of many taste and odorant molecules from complex processed foods [112,113,114,115,116,117,118]. Several csGPCRs have been deorphanized with in-vitro screening of odour- and taste-active compounds [26,119,120,121,122,123,124,125,126,127].…”
Section: Csgpcr Drug Discoverymentioning
confidence: 99%
“…Some studies have compared aged brandies according to their geographical origin from several countries such as China, France, Russia or Armenia . Uselmann and Schieberle have recently shown that the ratio of the concentration of ( E )‐β‐damascenone to ethyl pentanoate could be used to differentiate commercial brandies according to their country of origin (Germany, France or Spain). However, no study has been conducted to characterize samples in a limited geographic area of production.…”
Section: Introductionmentioning
confidence: 99%